PENGARUH EARNING PER SHARE (EPS), RETURN ON EQUITY (ROE), PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM PERUSAHAAN YANG GO PUBLIC DI BEI (Studi Empiris pada Perusahaan Industri Barang Konsumsi Yang Go Public di BEI Periode 2014-2015) - Permata Irmin Seriyarini; Ronny Malavia Mardani; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
This research is aimed to know the influence of Return on Equity (ROE), Earning per Share (EPS), Price Earning Ratio (PER) on stock returns. The population in this research are all the Consumer Goods Industry Companies that Go Public in Indonesian Stock Exchange 2014 to 2015 period. The sampling in this research is using purposive sampling technique with 35 companies. Techniques of analysis in this research using multiple linear regression to obtain a comprehensive picture of the relationship between variables. The results showed that Earning per Share (EPS) has positive effect but not significant on stock return of Consumer Goods Industry Companies that go public in IDX period 2014 to 2015 with regression coefficient 0,569 and the value of significant 0,00016. While Return On Equity (ROE) has positive effect and significant on stock returns with regression coefficient 1,52752 and the significant value 0,014. And then, Price Earning Ratio (PER) has negative effect and not significant on stock returns with regression coefficient -0,00333 and a significance value 0,296. The results showed Adjusted R2 of 17,3% that the contribution of EPS, ROE and PER to stock return is 17,3%.